The Fabrication of Polymer-Based Curcumin-Loaded Formulation as a Drug Delivery System: An Updated Review from 2017 to the Present - Abul Kalam Azad; Joanne Lai; Wan Mohd Azizi Wan Sulaiman; Hassan Almoustafa; Salah Abdalrazak Alshehade; Vinoth Kumarasamy; Vetriselvan Subramaniyan (MDPI AG, 2024)
Turmeric contains curcumin, a naturally occurring compound with noted anti-inflammatory and antioxidant properties that may help fight cancer. Curcumin is readily available, nontoxic, and inexpensive. At high doses, it has minimal side effects, suggesting it is safe for human use. However, curcumin has extremely poor bioavailability and biodistribution, which further hamper its clinical applications. It is commonly administered through oral and transdermal routes in different forms, where the particle size is one of the most common barriers that decreases its absorption through biological membranes on the targeted sites and limits its clinical effectiveness. There are many studies ongoing to overcome this problem. All of this motivated us to conduct this review that discusses the fabrication of polymer-based curcumin-loaded formulation as an advanced drug delivery system and addresses different approaches to overcoming the existing barriers and improving its bioavailability and biodistribution to enhance the therapeutic effects against cancer and other diseases.